Cities in European and Polish strategic documents - Kisielewicz, Beata (Miasta w europejskich i polskich dokumentach strategicznych, 2016)
Cities and urban areas have played greater and greater role in EU development process, and urban dimension is present in almost all European and Polish strategic documents. They establish development goals that cities should achieve and indicate problems they should focus on. The aim of the article is to summarize information relating to cities in European and Polish strategic documents over the last years and to create a vision of European and Polish city of the future
Biblioteka Regionalisty, 2016, Nr 16, s. 37-44
Keywords: European cities; regional development; urban policy; miasta europejskie; rozwój regionalny; polityka miejska